Teaching English Pronunciation through Phonetic Training: A Comparative Study Among English Teacher Trainees at the Open Educational College in Al-Suwaira, Wasit Province, Iraq - Ass.Lect Nada Shaker Al-Shammari (Journal of College of Education, 2025)
This study explores the importance of phonetic training in investigating the effectiveness of improving English pronunciation among teacher trainees at the Open Educational College in Al-Suwaira, Wasit Province. The research seeks to examine the effectiveness of a method of phonetic training to help prospective teachers to improve their abilities to produce speech sounds accurately, taking into account the contrasts between phonetic training and traditional pronunciation teaching. The research was carried out in two phases; pre-test and post-test including 50 EFL learners grouped into two. The participants were tested for correctly pronouncing the difficult consonants of English and clusters of consonants in English that are not present in Arabic (e.g., /p/, /ʒ/, /ŋ/ and /tʃ/). The study had two parts; a pre-test and a post-test were administered to 50 EFL learners in two groups. English Consonants and Consonant Clusters’ Production:It would be informative for second language researchers as well to see how participants produce the "hard" English consonants and consonant clusters’ selected in the present study (and which are not phonemic in Arabic), such as /p/, /ʒ/, /ŋ/, and /tʃ/. The majority of phoneme errors concerned phonological differences between Arabic and English, prevocalic consonant clusters and damage with consonant clusters, (see pre-test below) most commonly occurring as substitution errors. The accuracy of target pronunciation was considerably enhanced for the post-test after phonetic training.This is testament to the fact that the phonetic training program, which was informed by the use of the IPA for pronunciation instruction and the incorporation of targeted pronunciation exercise in course design, was more effective in obtaining impressive gains in accuracy of problem segments and in eliminating problematic errors than the traditional instruction. The findings of the study may imply that phonetic training offers the opportunity to improve pronunciation skills and consequently, the quality of English language teaching in Iraq, there is potential for enhancement in English language teaching skills and teacher trainees that, including future learners, which they will affect. In this sense the results of the research may also suggest that there is ample scope for phonetic training to be employed to raise pronunciation skills and, thereby, the quality of English language teaching in Iraq, and that English language teaching skills and teacher trainees and teachers, not to mention future learners, can be improved by such training.